IMPROVING STUDENTS' CRITICAL THINKING ABILITIES THROUGH PROBLEM SOLVING ON FRACTIONS IN GRADE V ELEMENTARY SCHOOL - Intan Zuhra; Fira A'dilla; Chandra Riski; Rahmatika; Mulia Aqsar; Yusnita; Kasmawati; Idariani; Nana Mulyana; Safriani; Muhammad Nur; Hasanuddin; Ety Mukhlesiyeni (RADJA PUBLIKA, 2026)
This study aims to determine students' critical thinking skills based on learning outcomes and analyze the differences between students' critical thinking skills and predetermined standard scores. This study uses a quantitative approach with descriptive analysis methods and hypothesis testing. The sample in this study amounted to 20 students. The research instrument used was a critical thinking skills test. Data analysis was carried out through a normality test using Shapiro-Wilk and a hypothesis test using the Wilcoxon Signed-Rank Test because the data did not meet the normality assumption. The results showed that the average value of students' critical thinking skills was 77.3, with a median value of 80.0 and a standard deviation of 8.66. Descriptively, the students' average score was above the comparison score, which was 75. The results of the normality test showed a significance value of 0.033 <0.05, so the data was declared not normally distributed. Furthermore, the results of the Wilcoxon test showed a significance value of 0.209 >0.05, so there was no significant difference between students' critical thinking skills and the predetermined standard scores. Based on the research results, it can be concluded that students' critical thinking skills are already in the good category descriptively, but the improvements obtained have not shown statistically significant differences. Therefore, the implementation of more active, innovative, and problem-solving-oriented learning strategies is needed to improve students' critical thinking skills.